Super-enhancers and efficacy of triptolide in small cell carcinoma of the ovary hypercalcemic type - Lang, Jessica; Selleck, William; Striker, Shawn; Hipschman, Nicolle A.; Kofman, Rochelle; Karnezis, Anthony N.; Kommoss, Felix; Kommoss, Friedrich; Wendt, Jae Rim; Facista, Salvatore J.; Hendricks, William P. D.; Orlando, Krystal A.; et al. (iScience, 2025)
Small cell carcinoma of the ovary-hypercalcemic type (SCCOHT) is a rare ovarian cancer affecting young females and is driven by the loss of both SWI/SNF ATPases SMARCA4 and SMARCA2. As loss of SWI/SNF alters enhancers, we hypothesized that super-enhancers, which regulate oncogene expression in cancer, are disparately impacted by SWI/SNF loss. We discovered differences between SWI/SNF occupancy at enhancers vs. super-enhancers. SCCOHT super-enhancer target genes were enriched in developmental processes, most notably nervous system development. This may further support neuronal cell-of-origin previously proposed. We found high sensitivity of SCCOHT cell lines to triptolide. Triptolide inhibits expression of many super-enhancer-associated genes, including oncogenes. SALL4 expression is decreased by triptolide and is highly expressed in SCCOHT tumors. In patient-derived xenograft models, triptolide and prodrug minnelide effectively inhibit tumor growth. These results reveal unique features of super-enhancers in SCCOHT, which may be one mechanism through which triptolide has high activity in these tumors.